PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS WEB MENGGUNAKAN GOOGLE SITES - Ummu Hanifah; Isna Rafianti, M.Pd (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
It was revealed that students' interest in learning mathematics is still low because students consider mathematics material difficult. Lack of utilization of learning media can be one of the factors in students' low understanding of mathematics subjects. Google sites is one of Google's products as a tool for creating websites that can be used in learning. This study aims to see the feasibility of web-based mathematics learning media using Google Sites and describe the steps and results of developing web-based mathematics learning media using Google Sites. The research method used is Research and Development (R&D) with the ADDIE development model consisting of Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 29 students of class X SMAN 3 Kota Serang. Data collection techniques were through interviews, observations, tests, and questionnaires. The results of the study showed that the average validation score of media experts obtained 89% and the average score of material experts obtained 97%. The results of the student response questionnaire obtained 87.96%, and the teacher obtained 98%. The results of the mathematical concept understanding test obtained 75.37%. Thus, web-based mathematics learning media using Google Sites is feasible, practical, and effective to be used as a learning medium, especially in mathematics subjects.